Noninvasive Measurement of Intra-Aneurysmal Pressure and Flow Pattern Using Phase Contrast with Vastly Undersampled Isotropic Projection Imaging - Moftakhar, R.; Aagaard-Kienitz, B.; Johnson, K.; Turski, P.A.; Turk, A.S.; Niemann, D.B.; Consigny, D.; Grinde, J.; Wieben, O.; Mistretta, C.A. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Currently, more reliable parameters to predict the risk of aneurysmal rupture are needed. Intra-aneurysmal pressure gradients and flow maps could provide additional information regarding the risk of rupture. Our hypothesis was that phase contrast with vastly undersampled isotropic projection reconstruction (PC-VIPR), a novel 3D MR imaging sequence, could accurately assess intra-aneurysmal pressure gradients in a canine aneurysmal model when compared with invasive measurements.MATERIALS AND METHODS: A total of 13 surgically created aneurysms in 8 canines were included in this study. Pressure measurements were performed in the parent vessel, aneurysm neck, and 5 regions within the aneurysmal sac with a microcatheter. PC-VIPR sequence was used to obtain cardiac-gated velocity measurements in a region covering the entire aneurysm. The velocity and pressure gradient maps derived from the PC-VIPR data were then coregistered with the anatomic DSA images and compared with catheter measurements.RESULTS: In 7 of the bifurcation aneurysms, the velocity flow maps demonstrated a recirculation flow pattern with a small neck-to-dome pressure gradient (mean, +0.5 mm Hg). In 1 bifurcation aneurysm, a flow jet extending from the neck to the dome with significantly greater pressure gradient (+50.2 mm Hg) was observed. All sidewall aneurysms had low flow in the sac with intermediate pressure gradients (mean, +8.3 mm Hg). High statistical correlation existed between PC-VIPR aneurysmal pressures and microcatheter pressure measurements (R = 0.82, P < .01).CONCLUSION: PC-VIPR can provide anatomic as well as noninvasive quantitative and qualitative hemodynamic information in the canine aneurysm model. The PC-VIPR intra-aneurysmal pressure measurements correlated well with catheter measurements.